Identification of Significant Prognostic Tissue Markers Associated with Survival in Upper Urinary Tract Urothelial Carcinoma Patients Treated with Radical Nephroureterectomy: A Retrospective Immunohistochemical Analysis Using Tissue Microarray - Kim, Sung Han (Cancer Res Treat, 2020)
PURPOSE: The purpose of this study was to identify prognostic tissue markers for several survival outcomes after radical nephroureterectomy among patients with upper urinary tract urothelial carcinoma using tissue microarray and immunohistochemistry. MATERIALS AND METHODS: Retrospectively, data of 162 non-metastatic patients with upper urinary tract urothelial carcinoma after radical nephroureterectomy between 2004 and 2016 were reviewed to determine intravesical recurrence-free survival (IVRFS), disease-free survival (DFS), and overall survival (OS). The expression of 27 tissue markers on a tissue microarray of radical nephroureterectomy samples and prognostic values of clinicopathological parameters were evaluated using immunohistochemistry and Cox proportional hazard models after adjusting for significant prognostic clinicopathological variables. The expression of all tissue markers was categorized into a binary group with continuous H-scores (0-300). RESULTS: Median follow-up was 53.4 months (range, 3.6 to 176.5 months); and, 58 (35.8%), 48 (29.6%), and 19 (11.7%) bladder recurrence, disease progression, and all cause death, respectively, were identified. After adjusting for significant clinicopathological factors including intravesical instillation for bladder recurrence-free survival, pathologic T category and intravesical instillation for disease progression-free survival, and pathologic T category for OS (p < 0.05), IVRFS was associated with epithelial cadherin (hazard ratio [HR], 0.49), epidermal growth factor receptor/erythroblastosis oncogene B (c-erb) (HR, 2.59), and retinoblastoma protein loss (HR, 1.85); DFS was associated with cyclin D1 (HR, 2.16) and high-molecular-weight cytokeratin (HR, 0.42); OS was associated with E-cadherin (HR, 0.34) and programmed cell death 1 ligand (HR, 13.42) (p < 0.05). CONCLUSION: Several significant tissue markers were associated with survival outcomes in upper urinary tract urothelial carcinoma patients treated with radical nephroureterectomy.